From Non-intervention to Positive Obligations: Addressing Privatised Political Interference under International Law - Bayer, Florian (Polish Review of International and European Law, 2025)
This article examines whether international law can address the issue of foreign political interference by powerful private actors whose actions distort public discourse, interfere with free and fair elections, and undermine public trust in democratic institutions. This encroaches upon the sovereignty of states. At the heart of the inquiry lies a structural tension: while international law focuses on the behaviour and accountability of states, the most disruptive forms of political influence today often originate from entities that lack governmental authority or recognised legal status. Therefore, the central question is whether international law can meaningfully engage with this emerging form of privatised interference and, if so, how. Firstly, the article analyses whether the principle of non-intervention, which lies at the core of protecting the sovereign equality of states, can be applied to such interferences. Secondly, it considers how the conduct of private actors can be attributed to a state. Finally, it explores whether other existing legal doctrines, most notably the no-harm principle and positive human rights obligations, can address the resulting accountability gap. Rather than offering definitive answers, the article highlights the limitations of a state-centric legal system when confronted with privatised power. At the same time, it outlines interpretive pathways through which international law might evolve to address this issue.